Providential Disorder in Plato’s Timaeus? - Maso, Stefano (Peitho. Examina Antiqua, 2018)
Plato tries to explain the becoming of the cosmos by referring to the concepts of order and disorder. Scholars have usually focused on the relationship between the cosmos and the demiurge that Plato puts forward to explain the reasonable (i.e., well-ordered) development. Along these lines, scholarship has examined the providential role played by both the demiurge and the soul of the world. Yet, an interesting problem still remains open: what exactly is the function of disorder? What is the sense of the concept of a perfectly established order if we do not know the manner in which it is achieved, since we have no understanding of the conditions that make it possible? Pursuing this line of thought, one may point to a providential role of the disorder given the balance of forces that operates in Plato’s cosmic becoming.